Burnout in clinicians working with offenders with personality disorder. Issue 2 (8th May 2017) - Chandler, Robert J.; Newman, Andrew; Butler, Catherine
Abstract : Purpose: The purpose of this paper is to examine the levels of clinician burnout in a community forensic personality disorder (PD) service, and explores how burnout may arise and be minimised within a service of this nature. Design/methodology/approach: A mixed methods approach was utilised, assessing levels of burnout and making comparisons with a comparable previous study. Focus group data regarding burnout and suggestions for reducing the risk of burnout were analysed using thematic analysis. Findings: Levels of burnout were generally found to be higher in the current sample when compared with the generic PD services. Qualitative data suggest that working in a forensic PD setting may pose a range of additional and complex challenges; these are explored in detail. Minimising burnout might be achieved by developing resilience, utilising humour, team coherence and ensuring that breaks are taken, and developing one's own strategies for "releasing pressure". Practical implications: The risk for burnout in clinicians working with offenders with PD may be higher than other groups of mental health clinicians. Despite this, attempts to minimise burnout can be made through a range of practical strategies at the individual, team and organisational level. Originality/value: This is the first project to assess levels of burnout specifically in a team of clinicians working with offenders with PD, and offers an exploration of how burnout may manifest and how it can be managed in this unique area of mental health.